Coulometric titration of water content and uptake in CAD/CAM chairside composites - Faria-e-Silva, Andre; Heckel, Lea; Belli, Renan; Lohbauer, Ulrich (Dental Materials, 2022)
Objectives: This study aimed to evaluate the water content and uptake of CAD/CAM chairside composites over 60 days using coulometric Karl Fischer (KF) titration. Methods: Rectangular plates (10 ×10×1 mm3 of thickness) were cut from the blocks of composites Cerasmart 270 (CS), Katana Avencia (KA), Grandio Blocs (GB), and Lava Ultimate (LU). Specimens were stored in distilled water for up to 60 days at 37 °C, and non-stored specimens were used as a control (n = 5). Specimens were isothermally heated at 200 °C, and the water content was evaporated and transferred to the titration cell throughout a nitrogen gas flow. The KF coulometer determined the percentage of water in each specimen. Data were analyzed by 2-way ANOVA and Tukey`s test (α = 0.05). Results: The water content of non-stored specimens ranged from 0.29 to 1.66 wt% (6.9–32.9 μg/mm3) for GB and LU, respectively. The water content increased underwater storage (0.82–2.96 wt% after 60 days). The extend of water sorption (11.9–26.1 μg/mm3) among the materials was directly related to their base water content. No additional water content increase was observed after 7 (LU and KA) or 21 (GB and CS) days. Measuring the water content in wt% or μg/mm3 affected the ranking of materials when KA and CS were analyzed. Significance: Composites with higher base water content also presented higher water sorption. KF titrationshowed to be a reliable method to measure the water sorption of composites, including their base water content.
CRIS-Team Scopus Importer:2022-05-06
Keywords: CAD/CAM; Karl Fischer titration; Resin composite; Water sorption